Safety Knows No Pause: Identifying the Relationship Between Disaster Literacy and Public Health Nurses’ Disaster Response Performance - Maala, Renmir Jan D.; Madano, Roselyn M.; Palwa, Yara M.; Vibas, Rene G. (Future Science / FSH-PH Publications, 2024)
This descriptive quantitative study aimed to identify the relationship between disaster literacy and the disaster response performance of public health nurses in various health institutions in Davao City. The research utilized a self-designed questionnaire survey, with participants providing details on their sex and years of experience. The survey comprised 10 questions assessing disaster literacy and 7 questions evaluating disaster response performance. Statistical analyses including Mann-Whitney U and Spearman were employed. Results showed a mean disaster literacy level of 3.91, categorized as high. However, no statistically significant relationship was found between disaster literacy and nurses' disaster response performance, regardless of sex and years of experience. Although a slight correlation of 0.135 between disaster literacy and performance was observed, it was not statistically significant (p=0.100), as indicated by the scatter plot analysis. Based on the findings of this study, researchers have devised disaster strategies. These strategies aim to equip all public health nurses to effectively respond to disasters, regardless of sex, experience, or prior knowledge. It involves creating a standardized disaster preparedness and response plan, conducting regular drills covering various scenarios, implementing ongoing education courses, and assigning roles based on skills rather than sex or experience, with clear documentation of responsibilities.